Phenolamides in plants: an update on their function, regulation, and origin of their biosynthetic enzymes. (14th December 2020) - Roumani, Marwa; Besseau, Sébastien; Gagneul, David; Robin, Christophe; Larbat, Romain
Abstract : We review the functional aspects of phenolamides in plants, the molecular regulation of their biosynthesis in response to biotic stress, and prospects for their phylogenetic origin through classification of N -hydroxycinnamoyltransferases Abstract: Phenolamides represent a family of specialized metabolites, consisting of the association of hydroxycinnamic acid derivatives with aliphatic or aromatic amines. Since the discovery of the first phenolamide in the late 1940s, decades of phytochemical analyses have revealed a high structural diversity for this family and a wide distribution in the plant kingdom. The occurrence of structurally diverse phenolamides in almost all plant organs has led to early hypotheses on their involvement in floral initiation and fertility, as well as plant defense against biotic and abiotic stress. In the present work, we critically review the literature ascribing functional hypotheses to phenolamides and recent evidence on the control of their biosynthesis in response to biotic stress. We additionally provide a phylogenetic analysis of the numerous N -hydroxycinnamoyltransferases involved in the synthesis of phenolamides and discuss the potential role of other enzyme families in their diversification. The data presented suggest multiple evolutionary events that contributed to the extension of the taxonomic distribution and diversity of phenolamides.